2009
DOI: 10.2466/pr0.105.1.87-98
|View full text |Cite
|
Sign up to set email alerts
|

Therapist Training, Feedback, and Practice for Dream Work: A Pilot Study

Abstract: Thirteen therapists (8 women, 5 men; M age = 29.1 yr., SD = 6.3; M counseling experience 2.7 yr., SD = 6.3, range = 1 semester to 8 yr.) received training in the cognitive-experiential model of dream work through a didactic-experiential workshop, individual feedback, and practice. All participants but one were enrolled in masters' or doctoral level counseling training programs. An examination of effect sizes indicated that (a) therapists' self-efficacy about using the dream model increased substantially and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In a recent empirical study with s small sample and only one trainer, Crook-Lyon et al (2009) found evidence that therapists felt more self-efficacy for working with dreams, had more positive attitudes toward dreams, and had higher self-reported competence for working with dreams as a result of training. In addition, there was some preliminary evidence that feedback from supervisors about their performance in sessions and practice doing sessions with clients both led to higher levels of self-efficacy, attitudes toward dreams, and ability to conduct dream sessions, but these findings await replication with larger samples.…”
mentioning
confidence: 99%
“…In a recent empirical study with s small sample and only one trainer, Crook-Lyon et al (2009) found evidence that therapists felt more self-efficacy for working with dreams, had more positive attitudes toward dreams, and had higher self-reported competence for working with dreams as a result of training. In addition, there was some preliminary evidence that feedback from supervisors about their performance in sessions and practice doing sessions with clients both led to higher levels of self-efficacy, attitudes toward dreams, and ability to conduct dream sessions, but these findings await replication with larger samples.…”
mentioning
confidence: 99%
“…Though dreamwork is not typically taught in graduate training programs, educators can consider dreamwork training. Therapists who completed a 3-hr CEDM workshop reported increased selfefficacy for using CEDM and positive attitudes toward dreams (Crook-Lyon et al, 2009). CEDM training resources include Dream Work in Practice (video; Hill, 2013) and Dream Work in Therapy: Facilitating Exploration, Insight, and Action (C. E. Hill, 2004).…”
Section: Training Implicationsmentioning
confidence: 99%
“…In addition, they suggested that training the trainers as well as trainees was integral to securing the systemic adoption of ROM (see Swift et al, 2015). Spangler and Sim (in press) reported that psychotherapists who received a 3-hr workshop on cognitive-experiential dream work increased their self-efficacy in using the cognitive-experiential dream model and their positive attitudes toward dreams (Crook-Lyon et al, 2009). …”
Section: Training Implicationsmentioning
confidence: 99%
“…Spangler and Sim (in press) reported that psychotherapists who received a 3-hr workshop on cognitive-experiential dream work increased their self-efficacy in using the cognitive-experiential dream model and their positive attitudes toward dreams (Crook-Lyon et al, 2009).…”
Section: Training Implicationsmentioning
confidence: 99%